The Husband's attendance at childbirth in Nepal: Experiences of women and their husbands, and the impact on birth outcomes and maternal emotional well-being of a new mother during postnatal period. - Sapkota, Sabitri (2012)
ABSTRACT: Childbirth is a physically and emotionally demanding process, and can involve a range of obstetric complications and medical interventions. Evidence suggests that these complications and interventions can be reduced by providing a parturient woman during labor with continuous support from close ones, including the husband. The benefit of continuous labor support has also been observed on the postnatal well-being of a new mother. However, labor support from the husband of a parturient woman is still new within the cultural values and norms of Nepalese society. Therefore, there is no clear understanding of the extent to which a parturient woman in Nepal can benefit from her husband's attendance at childbirth. This study aimed to examine the impact of the husband's attendance at childbirth on birth outcomes and on the maternal emotional well-being of a new mother during postnatal period. However, prior to this examination, a qualitative study was conducted to explore how Nepalese couples experience this new form of practice. First, in 2009, the women (n=12) and their husbands (n=12) were interviewed separately following the birth of a baby where the husband was present at childbirth. Then in 2011, an observational study was conducted to examine the impact of the husband's attendance at childbirth on the immediate birth outcomes, and on the emotional well-being of the new mother at 6 to 8 weeks postpartum. Low-risk primigravida women (n=298) at the time of their admission to the hospital were enrolled. These women were assisted at childbirth by either their husband or a female friend or no one. Women were followed until 6 to 8 weeks postpartum. Both studies were conducted in a public maternity hospital in Kathmandu, Nepal. The data were analyzed using thematic analysis, chi-square test and one-way analysis of variance (ANOVA) followed by post-hoc tests and regression analyses. The qualitative study described the women and their husband's mixed experiences, and they reported both positive and negative feelings. In particular, the women reported that the emotional support from their husbands outweighed their emotional discomfort, including their own hesitation and their concern for their husbands. Husbands, on the other hand, described their experiences positively but confessed that they had overwhelming emotional feelings. The observational study showed that women who had been accompanied by their husbands had experienced shorter labor (mean difference (95% CI),-122.14 minutes (-204.69, -39.59), p<0.01), a higher rate of spontaneous labor (92.8% vs. 80.0%, p<0.01), a higher score on the Labor Agentry Scale (LAS) (mean difference (95% CI), 11.24 (8.57, 13.91), p<0.001) and on postpartum support questionnaire (mean, 144.47 ± 36.77 vs. 121.58 ± 45.81, p<0.01) than the women without any companion. Additionally, compared to the women with a female companion, women accompanied by their husbands had also experienced shorter labor (mean difference (95% CI), -101.67 minutes (-184.23, -19.13), p<0.017) and a higher score for LAS (mean difference (95% CI), 8.01 (5.28, 10.70), p<0.001). The regression analyses confirmed that having the husband present at childbirth was significantly associated with a shorter labor (β=-0.15, p<0.05), spontaneous labor (OR=3.71, p<0.01), women's increased sense of labor control (β=0.57, p<0.001) and a higher degree of postnatal support (β=0.17, p<0.01). Although some emotional discomfort was described by the women and their husbands in the first study, the second clearly demonstrated many positive outcomes related to both birth outcomes and the emotional well-being of a new mother during postnatal period. This shows that despite the husband's attendance at childbirth being a new concept in the cultural context of Nepal, the women benefited from it. Nonetheless, to reduce a couple's emotional discomfort and enhance a new mother's emotional well-being, provision of antenatal education and labor support skills are recommended for the husband prior to his attendance at childbirth.